Efektivitas Brainstorming dalam Meningkatkan Hasil Belajar Aqidah Akhlaq Siswa Kelas VII MTs Ismailiyah Ngusikan Jombang - Zilfi Mumtaza; Rohmat Hidayat; Hilyah Ashoumi (Lembaga Yasin AlSys, 2026)
Although the brainstorming method has received attention in a number of studies related to improving students’ activity and critical thinking skills, studies that specifically discuss its effectiveness in overcoming managerial constraints, such as limited learning resources in the form of textbooks and the lack of teacher linearity in the Aqidah Akhlak subject, remain limited. This study aims to describe the implementation of the brainstorming method and analyze its effectiveness in improving the Aqidah Akhlak learning outcomes of seventh-grade students. This study used a quantitative approach with a quasi-experimental design of the One-Group Pretest-Posttest Design type. This study involved seventh-grade students of MTs Ismailiyah Ngusikan Jombang as participants selected in accordance with the needs of the research subjects. Data were collected through observation, interviews, and learning outcome tests, and were then analyzed using the Paired Samples T-Test and the N-Gain test. The results showed a statistically significant improvement in learning outcomes with a Sig. (2-tailed) value of 0.000 < 0.05, in which the students’ mean score increased from 56.08 to 89.08. Based on the N-Gain test, a value of 74.96% was obtained, indicating that this method falls into the effective category with a high-level classification of improvement in learning outcomes. This finding contributes to the development of innovative learning theory and expands understanding of the importance of students’ active cognitive engagement in the context of religious education. The conclusion of this study emphasizes the importance of the teacher’s role as a facilitator in stimulating students’ critical capacity and independence despite limitations in learning facilities. The implications of this study include a theoretical contribution to enriching the literature on learning strategies in secondary schools as well as practical implications for educational institutions in overcoming barriers related to physical learning resources through collaborative mental activities. This study also opens opportunities for further research on integrating the brainstorming method with technology-based learning media for broader material coverage.